2021
DOI: 10.3389/fmolb.2021.649169
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of Non-invasive Prenatal Testing to Detect Fetal Chromosomal Copy Number Variations

Abstract: Non-invasive prenatal testing (NIPT) for common fetal trisomies is effective. However, the usefulness of cell-free DNA testing to detect other chromosomal abnormalities is poorly understood. We analyzed the positive rate at different read depths in next-generation sequencing (NGS) and identified a strategy for fetal copy number variant (CNV) detection in NIPT. Pregnant women who underwent NIPT by NGS at read depths of 4–6 M and fetuses with suspected CNVs were analyzed by amniocentesis and chromosomal microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Twenty-five of the 63 included studies (39.7%) involved predominately high-risk cohorts. 15,26,28,29,31,35,37,39,41,42,45,51,54,56,57,59,60,62,65,67,71,[73][74][75]78 Six inclusions (9.5%) were validation studies assessing novel cfDNA technologies or algorithms. 15,29,31,39,47,49 Seventeen studies (27.0%) reported cfDNA screening outcomes for 22q.11.2 syndrome (16 reporting PPV 12,14,26,27,30,38,40,47,56,60,65,68,69,73,76,83 and three reporting sensitivity and specificity 39,60,76 ), inc...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-five of the 63 included studies (39.7%) involved predominately high-risk cohorts. 15,26,28,29,31,35,37,39,41,42,45,51,54,56,57,59,60,62,65,67,71,[73][74][75]78 Six inclusions (9.5%) were validation studies assessing novel cfDNA technologies or algorithms. 15,29,31,39,47,49 Seventeen studies (27.0%) reported cfDNA screening outcomes for 22q.11.2 syndrome (16 reporting PPV 12,14,26,27,30,38,40,47,56,60,65,68,69,73,76,83 and three reporting sensitivity and specificity 39,60,76 ), inc...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…On the contrary, Kaseniit et al, in a 2018 study, reported how, with proper algorithm design and extensive testing, NIPT can achieve high specificity also for CNV alterations [ 52 ]. Songchan et al, in a 2021 study, highlight how an adequate analysis as an NGS method, can be very valid as long as the depth of reading is adequate; this in fact allows us to reduce the percentage of false positives and consequently increase the specificity of the test [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A major issue with CNV lies in the fact that many alterations detected, in the case of a shallow NGS sequencing, risk not being confirmed and are therefore false positives. Instead, using NGS sequencing of adequate depth could provide an adequate method to detect CNVs with relatively advantageous costs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CNVs identified by NIPT could be larger or smaller in size than those detected by CMA [Li et al, 2016]. NIPT can provide a good indication of chromosomal imbalances, but the detection is influenced by read counts, type of algorithm, and fetal fraction [Chen et al, 2021]. For a positive NIPT result, further diagnostic investigation is needed to identify the genomic position of chromosomal imbalances at higher precision, and CMA should be performed as a gold standard to confirm the presence of CNVs reported by NIPT.…”
Section: Discussionmentioning
confidence: 99%